Perunika – cvet nebeskog ili htonskog sveta?German Iris – The Flower from the Heavenly or Chthonian World? - Radenković, Ljubinko (Studia mythologica Slavica, 2013)
<span style="line-height: 115%; font-family: 'Calibri','sans-serif'; font-size: 11pt; mso-ascii-theme-font: minor-latin; mso-fareast-font-family: Calibri; mso-fareast-theme-font: minor-latin; mso-hansi-theme-font: minor-latin; mso-bidi-font-family: 'Times New Roman'; mso-bidi-theme-font: minor-bidi; mso-ansi-language: SL; mso-fareast-language: EN-US; mso-bidi-language: AR-SA;">For more than a century, scholars of Slavic mythology have adopted the assumption connecting the German iris (Iris germanica) plant and the cult of the god Perun. The motivation for this connection was mainly found in two (of several dozen) South Slavic names for this plant, “perunika” and “bogiša”, as well as certain calendar customs where it is used. Among other things, this paper considers the main arguments of the advocates of this thesis. Based on the presented less-known facts about the role of this plant in the folklore of the South Slavic peoples, the author concludes that there are no grounds for linking the plant to the cult of Perun, the god of thunder. The motivation for the name “perunika” comes from its dominant feather-like (perasti) leaves, the name “bogiša” (bog, Eng. god) is only one of the narrowly local names (from the vicinity of Dubrovnik).